Fist of the North Star. Volume 9 - Buronson, 1947- (VIZ Media, LLC, 2023)
"In a postapocalyptic world, humanity has risen from the ashes of all-out nuclear war to a nightmare of endless suffering. It is a time of chaos. Warlords and gangs of savage marauders rule the broken ruins of civilization, terrorizing and enslaving the survivors. Life has become a brutal struggle for existence and death the only release. After an epic contest, Kenoh leaves his brothers to begin a new reign of terror in the wasteland. But while he was away, Ryuga, one of his lieutenants, turned against him and established his own stronghold. Ken and Toki head there to find out what Ryuga knows about Kenoh. The one force that may still stand against Kenoh is the Goshasei, the Guardian Stars of Nanto, and their last general, whose secret will bring Kenshiro face-to-face with those he thought he'd lost..."--Back cover.